PENGARUH INOVASI SAHABAT LAPOR TERHADAP KUALITAS PELAYANAN PUBLIK DI SEKRETARIAT DAERAH KABUPATEN GOWA - Antonio, Jefri Julien; Hakim, Lukman; Yusuf, Muhammad (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the effect of Sahabat Report's innovation on the quality of public services at the regional secretariat of Gowa Regency, innovation is an idea or idea that was born due to a lack of something that already exists. The research method used is quantitative with descriptive type. The data collection technique used a questionnaire/questionnaire distributed to 50 respondents. Analysis using simple linear regression using the SPSS 25 application. The results of this study indicate that there is a positive and significant effect of service innovation on service quality, namely the regression coefficient value for the variable is 1.130 with a significance value of 0.000. The significant value of 0.000 is smaller than 0.05, indicating that innovation has a significant influence on the quality of public services with a positive regression coefficient direction, so there is an influence of the Service Innovation variable (X) on the Service Quality variable (Y).